Educational Manga Series: Pseudo-Interactive Effect in Learning Mathematics through Modular Distance Learning - Victorina de Torres Palanas; Dexter Palanas (JPAIR Institutional Research Journal)
The education disruption has had and will continue to have substantial effects beyond education. The closure of schools worldwide became a signal to implement distance or remote learning.  However, online learning modalities were associated with positive impact and effectiveness due to their feasible variables, such as assessment and interaction. Most learners still choose modular distance learning modality due to the lack of available materials and internet access. This study aims to develop an educational manga series in Mathematics that will minimize the learning gaps and create a pseudo-interactive effect on learners to increase their interest in reading and understanding printed modules. Mixed-Method Research Design, specifically sequential explanatory design, was used to ensure the successful implementation of the intervention continually. Data was collected and interpreted using google forms and a focus group discussion (FGD) afterward via google meet. Based on the findings, it was found that manga can help the learners grasp the meaning of the text better; as learning material, it can enhance understanding of the Mathematics concept and instruction better. The illustration and story help the learners increase their motivation and excitement due to their pseudo-interactive effect. This effect is described as the feeling of being part of the story. Therefore, it is recommended to use educational manga as learning materials in flexible learning options (FLOs) and courses that require practical experience.